FeCl3-Catalyzed Aerobic Oxidative Degradation of Polystyrene to Benzoic Acid: Scope and Mechanism - Zhang, Guoxiang; Xue, Ting; Wang, Liting; Wang, Sichang; Ke, Congyu; Zeng, Rong (Synlett, 2024)
Chemical upcycling of polystyrene (PS) is one of the most promising approaches to plastic waste reuse and to achieve economic development goals. However, it remains a huge challenge because PS has only chemically inert covalent bonds. As part of an ongoing study, we herein describe the development, scope, and mechanism of photoinduced iron catalysis for the selective oxidative degradation of polystyrene to benzoic acid. A series of commonly found polystyrene products could be degraded to benzoic acid efficiently. A plausible mechanism involving radical-based stepwise aerobic oxidation was proposed.
Keywords: polystyrene; degradation; iron catalysis; photocatalysis; plastic upcycling